2023
DOI: 10.1021/jacs.2c13198
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Pyruvate Chemical Conversion Monitoring Enabled by PHIP

Abstract: In recent years, parahydrogen-induced polarization side arm hydrogenation (PHIP-SAH) has been applied to hyperpolarize [1-13C]­pyruvate and map its metabolic conversion to [1-13C]­lactate in cancer cells. Developing on our recent MINERVA pulse sequence protocol, in which we have achieved 27% [1-13C]­pyruvate carbon polarization, we demonstrate the hyperpolarization of [1,2-13C]­pyruvate (∼7% polarization on each 13C spin) via PHIP-SAH. By altering a single parameter in the pulse sequence, MINERVA enables the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This spin order is transferred to the molecule of interest by a method, which is called parahydrogen-induced polarization by means of side-arm hydrogenation (PHIP-SAH) [22]. Since its introduction in 2015 by Reineri et al, it has found broad application [23][24][25][26][27][28][29][30][31][32]. The workflow applied here is depicted in Fig.…”
Section: Applied Magnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…This spin order is transferred to the molecule of interest by a method, which is called parahydrogen-induced polarization by means of side-arm hydrogenation (PHIP-SAH) [22]. Since its introduction in 2015 by Reineri et al, it has found broad application [23][24][25][26][27][28][29][30][31][32]. The workflow applied here is depicted in Fig.…”
Section: Applied Magnetic Resonancementioning
confidence: 99%
“…The aqueous 1 3 Hyperpolarized Multi-organ Spectroscopy of Liver and Brain… solution containing clean hyperpolarized pyruvate was ready to be injected. A more detailed description on the procedure was previously described [31][32][33].…”
Section: Hyperpolarizationmentioning
confidence: 99%
“…28 Alkyne esters represent an important class of targets as they offer the possibly to hyperpolarize a range of carboxylate containing molecules such as pyruvate or lactate via the side-arm hydrogenation (PHIP-SAH) strategy. [29][30][31][32] Here we study the production of hyperpolarized allyl acetate (AL) as shown in Fig. 1a.…”
Section: Introductionmentioning
confidence: 99%
“…A faster and simpler approach to hyperpolarize [1-13 C]pyruvate is parahydrogen-induced polarization (PHIP). 38,[51][52][53] One possibility is side-arm hydrogenation PHIP (SAH-PHIP), 54,55 which has been successfully used to hyperpolarize [1-13C]pyruvate, [56][57][58] the most common hyperpolarized MRI tracer. In SAH-PHIP an unsaturated side arm of a pyruvate ester is hydrogenated with parahydrogen, the polarization is transferred to the 13 C nucleus, and the pyruvate is then cleaved via hydrolysis of the ester.…”
Section: Introductionmentioning
confidence: 99%